2014
DOI: 10.3389/fpsyg.2014.00002
|View full text |Cite
|
Sign up to set email alerts
|

Intensive exposure to narrative in story books as a possibly effective treatment of social perspective-taking in schoolchildren with autism

Abstract: One of the major characteristics of autism is impairment of communication and socialization. While such impairment per se has been well documented, research into effective interventions for children with this developmental disorder is still limited. Here we present preliminary evidence for the possibility of improvement of the capability of social perspective-taking in schoolchildren with autism by having intensive experience with narrative, in which they were exposed to narrative in story books read by their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 33 publications
0
10
1
Order By: Relevance
“…In addition to the obvious communicative benefits of bilingualism, there has been some evidence suggesting a bilingual advantage in executive control across both linguistic and nonlinguistic domains ( e.g . Bialystok, Craik, Green, & Gollan, 2009; but see Paap & Sawi, 2014 for an alternative view). Of particular importance is L2 vocabulary acquisition, an integral part of L2 learning that predicts lexical richness in language production, verbal fluency, reading ability, and reading comprehension (Nation, 1993; Laufer & Nation, 1995; Luo, Luk, & Bialystok, 2010; Qian, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the obvious communicative benefits of bilingualism, there has been some evidence suggesting a bilingual advantage in executive control across both linguistic and nonlinguistic domains ( e.g . Bialystok, Craik, Green, & Gollan, 2009; but see Paap & Sawi, 2014 for an alternative view). Of particular importance is L2 vocabulary acquisition, an integral part of L2 learning that predicts lexical richness in language production, verbal fluency, reading ability, and reading comprehension (Nation, 1993; Laufer & Nation, 1995; Luo, Luk, & Bialystok, 2010; Qian, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The final section of the series takes a more applied angle. Two papers (Adlof et al, 2014;Tsunemi et al, 2014) present preliminary data from interventions using story books that show promise in helping children improve key skills. Adlof et al (2014) confirmed the feasibility of a new intervention for low-SES children: structured narrative retell instruction (SNRI).…”
Section: Interventions Using Story Booksmentioning
confidence: 99%
“…Children who completed the intervention showed improvements in narrative macrostructure (including the total number and diversity of the words they used and their mean length of utterance) and overall vocabulary scores. Tsunemi et al's (2014) intervention aimed to help school-aged children with autism improve their social perspective-taking skills. Parents read narrative books to their children for almost a week and asked questions about the mental states of the characters after each reading.…”
Section: Interventions Using Story Booksmentioning
confidence: 99%
“…The final section of the series takes a more applied angle. Two papers (Adlof et al, 2014 ; Tsunemi et al, 2014 ) present preliminary data from interventions using story books that show promise in helping children improve key skills. Adlof et al ( 2014 ) confirmed the feasibility of a new intervention for low-SES children: structured narrative retell instruction (SNRI).…”
Section: Interventions Using Story Booksmentioning
confidence: 99%